Intercountry Adoption in Malaysia and Morocco: A New Frontier - A. Kadir, Nadhilah; Mohd, Azizah (Hasanuddin Law Review, 2023)
Intercountry adoption offers a family-based care option for children in need of care and protection. It allows them to find loving and permanent homes outside their birth country, providing them with stability, support, and a sense of belonging essential for their well-being. The Hague Convention on Protection of Children and Cooperation in Respect of Intercountry Adoption 1993 (Hague Convention 1993) serves as the primary international legal instrument governing intercountry adoption. Despite its importance, intercountry adoption remains relatively uncommon in Malaysia, as the country lacks specific statutory provisions and is not a signatory to the Hague Convention 1993. The purpose of this study is to examine the current state of intercountry adoption in Malaysia and Morocco and explore the viability of intercountry adoption as a child protection measure. The study involves interviews with relevant departments and an examination of Malaysia's current adoption laws. Additionally, the study analyses the international legal framework, including the Hague Convention 1993 and the United Nations Convention on the Rights of the Child 1989 (UNCRC) to provide a comprehensive understanding of the context surrounding intercountry adoption. Furthermore, this paper offers a comparative analysis of Morocco's intercountry kafalah system, which recognises kafalah as an alternative to legal adoption based on Islamic law. The findings of this study will offer valuable insights and recommendations for enhancing Malaysia's approach to intercountry adoption. By considering best practices and international standards, this research seeks to ensure the well-being and protection of children in need of care and protection, promoting their access to a stable and nurturing family environment.